A new species of Metrobates Uhler, 1871 (Hemiptera: Heteroptera: Gerridae) from Colombia - Castro-Vargas, Maria I.; Morales, Irina; Molano-Rendón, Fredy (Zootaxa, 2018)
A new species of Metrobates Uhler, 1871 (Trepobatinae: Metrobatini) from Colombia is described. Metrobates sanciprianensis sp. nov. resembles M. fugientis Drake & Harris but is distinguished by the shape of the parameres and the lack of a spine on the fore femur. In addition, M. amblydonti Nieser is redescribed and a key to males of the species of Metrobates in Colombia is presented.